Assessment Of Clinical Outcome Of Cyanoacrylate Glue Versus Suture Fixation Of Mesh In Ventral Hernia - Dr Sharmila V; Dr Pola Govardhan kumar; Dr Ramalakshmi V (International Journal of Medical Toxicology and Legal Medicine, 2024)
Ventral hernia repair(VHR) traditionally involves mesh placement to reinforce the abdominal wall. Current research attempts to evaluate the clinical results of cyanoacrylate glue versus conventional suture fixation for anchoring the mesh in VHR. The research evaluates both techniques regarding operative time span, postoperative pain, duration of hospitalization, complication incidence, as well as recurrence rates. Patients were assigned by randomization into 2groups: one having cyanoacrylate glue fixation &other receiving suture fixation. Results indicate that cyanoacrylate glue significantly reduces operative time and postoperative pain, with no significant increase in recurrence or complications. The findings suggest that Cyanoacrylate glue is safe & effective alternative to sutures in mesh fixation, improving patient comfort and recovery while maintaining comparable outcomes in terms of hernia recurrence and complications. Additional research recommended to confirm long-term outcomes of CA glue fixation in hernia repair.